Amino Acid Derivatives as New Zinc Binding Groups for the Design of Selective Matrix Metalloproteinase Inhibitors. (10th March 2013) - Giustiniano, Mariateresa; Tortorella, Paolo; Agamennone, Mariangela; Di Pizio, Antonella; Rossello, Armando; Nuti, Elisa; Gomez-Monterrey, Isabel; Novellino, Ettore; Campiglia, Pietro; Vernieri, Ermelinda; Sala, Marina; Bertamino, Alessia; et al.
Abstract : A number of matrix metalloproteinases (MMPs) are important medicinal targets for conditions ranging from rheumatoid arthritis to cardiomyopathy, periodontal disease, liver cirrhosis, multiple sclerosis, and cancer invasion and metastasis, where they showed to have a dual role, inhibiting or promoting important processes involved in the pathology. MMPs contain a zinc (II) ion in the protein active site. Small-molecule inhibitors of these metalloproteins are designed to bind directly to the active site metal ions. In an effort to devise new approaches to selective inhibitors, in this paper, we describe the synthesis and preliminary biological evaluation of amino acid derivatives as new zinc binding groups (ZBGs). The incorporation of selected metal-binding functions in more complex biphenyl sulfonamide moieties allowed the identification of one compound able to interact selectively with different MMP enzymatic isoforms.